2007
DOI: 10.1021/jf071520h
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene Induces Apoptosis and Cell Cycle Arrest in Human Gastric Carcinoma Cells

Abstract: Pterostilbene, an active constituent of blueberries, is known to possess anti-inflammatory activity and also induces apoptosis in various types of cancer cells. Here, the effects of pterostilbene on cell viability in human gastric carcinoma AGS cells were investigated. This study demonstrated that pterostilbene was able to inhibit cell proliferation and induce apoptosis in a concentration- and time-dependent manner. Pterostilbene-induced cell death was characterized with changes in nuclear morphology, DNA frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 34 publications
8
108
1
Order By: Relevance
“…These data suggest that resveratrol inhibits the proliferation of cancer cells through the modification of Cyclin-CDK complexes, Rb protein expression, E2F transcription factors, led to a cell cycle arrest and the inhibition of proliferative activity. Pan et al (2007) investigated the effect of pterostilbene in human gastric carcinoma cells and found that pterostilbene inhibits the cell proliferation and induce apoptosis by the modification of Cyclin-CDK complexes and modifying cell cycle progress similar to that of resveratrol. Pterostilbene increased the p53, p21, p27, and p16 protein levels and decreased the levels of Cyclin A, Cyclin E, CDK2, CDK4, and CDK6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that resveratrol inhibits the proliferation of cancer cells through the modification of Cyclin-CDK complexes, Rb protein expression, E2F transcription factors, led to a cell cycle arrest and the inhibition of proliferative activity. Pan et al (2007) investigated the effect of pterostilbene in human gastric carcinoma cells and found that pterostilbene inhibits the cell proliferation and induce apoptosis by the modification of Cyclin-CDK complexes and modifying cell cycle progress similar to that of resveratrol. Pterostilbene increased the p53, p21, p27, and p16 protein levels and decreased the levels of Cyclin A, Cyclin E, CDK2, CDK4, and CDK6.…”
Section: Resultsmentioning
confidence: 99%
“…These effects were observed in association with the loss of mitotoxic and metastatic potential of MCF-7 cells, which was abolished in the presence of catalase and autophagic inhibitor. Another study on gastric cancer carcinoma showed that pterostilbene causes increased ROS, which altered mitochondrial transmembrane potential, causing release of cytochrome-c, followed by activation of caspase triggering programmed cell death (Pan et al 2007). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most known stilbenoid derivative is trans-resveratrol (16, 3,5,4'-trihydroxystilbene, Table 2), isolated from a large variety of plants and found in the diet as for example in red wine, peanuts, mulberries and grapes [40]. Red wine contains 1.5 to 3.0 mg of resveratrol per 1 L. Trans-pterostilbene (17), another stilbenoid derivative reported to target kinase activity, is shown in Table 2 [41,42].…”
Section: Group Ii: Stilbenoid Derivativesmentioning
confidence: 99%
“…Additionally, protein kinase C (PKC) was targeted by this polyphenol as part of the process resulting in the inhibition of oncogene signal transduction [41]. Pterostilbene (17), a natural analogue of resveratrol (16), was reported to induce apoptosis and cell cycle arrest in human gastric carcinoma cells and this anticancer effect was associated with the down-regulation of cyclin-dependent kinase 2 (Cdk2), Cdk4 and Cdk6 [42]. Wilson et al [96] recently reported toxicity towards Caenorhabditis elegans adults for trimethoxylated and dimethoxylated stilbenes, as well as the monomethoxylated stilbene desoxyrhapontigenin.…”
Section: Group Ii: Stilbenoid Derivativesmentioning
confidence: 99%